Differences in Granule Morphology yet Equally Impaired Exocytosis among Cytotoxic T Cells and NK Cells from Chediak–Higashi Syndrome Patients - Chiang, Samuel C. C.; Wood, Stephanie M.; Tesi, Bianca; Akar, Himmet Haluk; Al-Herz, Waleed; Ammann, Sandra; Belen, Fatma Burcu; Caliskan, Umran; Kaya, Zühre; Lehmberg, Kai; Patiroglu, Turkan; Tokgoz, Huseyin; et al. (Frontiers in Immunology, 2017)
Chediak-Higashi syndrome (CHS) is caused by autosomal recessive mutations in LYST, resulting in enlarged lysosomal compartments in multiple cell types. CHS patients display oculocutaneous albinism and may develop life-threatening hemophagocytic lymphohistiocytosis (HLH). While NK cell-mediated cytotoxicity has been reported to be uniformly defective, variable defects in T cell-mediated cytotoxicity has been observed. The latter has been linked to the degree of HLH susceptibility. Since the discrepancies in NK cell- and T cell-mediated cellular cytotoxicity might result from differences in regulation of cytotoxic granule release, we here evaluated perforin-containing secretory lysosome size and number in freshly isolated lymphocytes from CHS patients and furthermore compared their exocytic capacities. Whereas NK cells from CHS patients generally contained a single, gigantic perforin-containing granule, cytotoxic T cells predominantly contained several smaller granules. Nonetheless, in a cohort of 21 CHS patients, cytotoxic T cell and NK cell granule exocytosis were similarly impaired upon activating receptor stimulation. Mechanistically, polarization of cytotoxic granules was defective in cytotoxic lymphocytes from CHS patients, with EEA1, a marker of early endosomes, mislocalizing to lysosomal structures. The results leads to the conclusion that lysosome enlargement corresponds to loss of distinct organelle identity in the endocytic pathway, which on a subcellular level more adversely affects NK cells than T cells. Hence, vesicular size or numbers do not per se dictate the impairment of lysosomal exocytosis in the two cell types studied.